Solar Dish - Qasem Basem Malhis; Qusai Ali Abdalwahab AbdlAalrahman; Malek Mohammad Abbas; Odai Jamal Wahdan (My University, 2014)
The aim of this project is to design Solar Dish Engine for heating water from the sun. Dish/engine systems convert the thermal energy in solar radiation to heating water, dish/engine systems use a mirror array to reflect and concentrate incoming direct normal isolation to a heat exchanger, in order to achieve the temperatures required to efficiently convert heat to.  This requires that the dish track the sun in two axes by two sensor at the dish one in the east and the other in the west. The concentrated solar radiation is absorbed by the receiver and transferred to a tank.